A Brief Overview on Chamomile - Sachin Aglawe; Amol Gayke; Kavita Sharma; Deven Aspalani; Chandrashekar Wake (Current Overview on Pharmaceutical Science Vol. 1, 2022)
Chamomile (Matricaria chamomilla L.) is a popular spice and herb used all over the world. They include flavonoids and hydroxycinnamates, both of which have the potential to benefit human health. This article provides a brief overview of the therapeutic benefits, as well as botany and cultivation practices. Because chamomile has a wealth of natural products, information on the chemical elements of essential oils and plant parts, as well as their pharmacological effects, is provided. Chamomile is primarily used as an anti-inflammatory and antiseptic, as well as an antispasmodic and mild sudorific. Chamomile preparations are widely used to treat a wide range of human problems, including hay fever, inflammation, muscular spasms, menstrual disorders, sleeplessness, ulcers, wounds, gastrointestinal disorders, rheumatic pain, and hemorrhoids. In children, there are rarely side effects. Children who are allergic to ragweed, asters, or chrysanthemums should avoid chamomile. According to the researchers, the pharmacological activity of German chamomile is primarily related to its essential oils. Chamomile’s active ingredients can be altered by environmental factors and circumstances.